Membrane and centrifugal therapeutic plasma exchange: practical difficulties in anticoagulating the extracorporeal circuit - Puppe, B. (Clin Kidney J, 2014)
Therapeutic plasma exchange (TPE) is a well-established treatment modality for nephrology patients, using two conventional methods: membrane (mTPE) or centrifugal TPE (cTPE). Although the efficacy of both treatments has been described, there are few reports that compare these methodologies. Here we describe three nephrology patients who were treated with both mTPE and cTPE. The mTPE method, but not the cTPE method, was associated with persistent difficulty anticoagulating the extracorporeal circuit in all three patients. In mTPE procedures, the doses of heparin bolus and infusion rate were important determinants of whether the circuit clotted. With a heparin bolus at or below 2000 IU, clotting occurred in 67% of treatments, dropping to 25% with a bolus of >2000 IU. Likewise, a heparin infusion rate during the procedure was indicative of clotting. With a maintenance infusion of <2000 IU/h, most circuits clotted. No clotting was observed during cTPE procedures using acid citrate dextrose formula A solution as an anticoagulant of the extracorporeal circuit. Overall, difficulties maintaining the extracorporeal circuit in mTPE required the use of additional disposable sets, high doses of heparin and nursing time. In addition, mTPE procedures took longer to perform than cTPE.